Comparison of surface topography of low-friction and conventional TMA orthodontic arch wires using atomic force microscopy - Nouf I Alsabti; Christoph P Bourauel; Nabeel F Talic (Wolters Kluwer Medknow Publications, 2021)
OBJECTIVE: To evaluate the surface topography and roughness of orthodontic arch wire materials, including low-friction titanium molybdenum alloy (TMA), conventional TMA, and stainless-steel arch wires. MATERIALS AND METHODS: The surface topography was evaluated using atomic force microscopy (AFM). A total of 24 wire specimens were used for the AFM scans {8 low-friction TMA (TMA-Low), 8 conventional TMA (TMA-C), and 8 stainless steel (SS)} (Ormco, Orange, CA, USA), measuring 0.016 × 0.022 inches. The conventional and low-friction TMA arch wires served as the test groups, while the stainless-steel arch wire served as the control group. RESULTS: Surface roughness evaluation using AFM revealed that the highest mean of all three roughness parameters was found in the TMA-C group followed by the TMA-Low and SS arch wires in descending order. Pairwise comparison of the mean values showed that the mean value of the SS arch wire material is statistically significantly lower than the mean values of the other two arch wire materials (TMA-C and TMA-Low). However, there was no statistically significant difference in the mean values of TMA-C and TMA-Low arch wires. CONCLUSION: The SS arch wire showed the smoothest surface topography among the alloys and had statistically significantly lower roughness values than the TMA-C and TMA-Low groups. Low-friction TMA arch wire is still considered to be inferior to stainless steel arch wire.